Perypetie Maksymiana, czyli o paratekstach, zmienności gustów czytelniczych i łabędzim śpiewie elegii rzymskiej - Wasyl, Anna Maria (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
Varied were the vicissitudes of Maximianus, whose unique opus elegiacum marks a swan song of sorts of the Roman elegy. No less interesting, however, are the changes in the reception of this text, i.e., following H.R. Jauss’s understanding of the term, in the modes of its interpretation by readers through the centuries. They can be efficiently traced by analyzing varied codicological data and, in particular, some paratexts (introductory notes/accessus, marginal notations, tituli, subscriptiones etc.) accompanying the author and his work as transmitted in a manuscript or an early printed book. Such data provide also us with a great deal of information concerning the generic classification of a text, as based on the Erwartungshorizont, or the horizon of expectations of its literary audience at a certain moment in history. As I demonstrate throughout my article, the historical flexibility of the interpretations of Maximianus’s opus is an excellent example of the above-mentioned phenomenon.